Flowering and Fruiting Times on Four Species of Annona (Annonaceae) in Purwodadi Botanic Garden - Dewi Ayu Lestari; Siti Sofiah (Journal of Tropical Life Science, 2015)
Annona is a genus belongs to Annonaceae family, consisting of numerous species that produce edible fruit.   Four species namely A. glabra, A. montana, A. muricata and A. squamosa collections of Purwodadi Botanic Garden  were recorded for its flowering and fruiting times, since November 2010 to April 2013. The data were scored and complemented with climate data (temperature, rainfall intensity, humidity) then analyzed using multiple linear regression analysis.  The result showed that humidity was the most affected climate factors on the flowering and fruiting times of those species.  Specifically, rainfall intensity (0-550 mm) affected to  Annona muricata, temperature (25,56-28,33 °C) and humidity (66,83-85,02%) to  Annona squamosa, and  humidity to  A. glabra (71,62-85,02% )  and  A. montana (71,62 to 82,94 %) as well. Flowering time of A. glabra occurs three times a year in wet and dry, and fruiting occurs twice a year in the same month. Annona muricata is flowering throughout the year and fruiting twice a year in wet. A. montana and A. squamosa recorded one a year during the wet month.